Alteration in PNMA1 expression is associated with poor prognosis and tumor immune infiltration in head and neck squamous cell carcinoma - Dakshitha Sankar; Balachander Kannan; Vijayashree Priyadharsini Jayaseelan; Jeevitha Manicka Vasagam; Paramasivam Arumugam (Journal of Oral Biology and Craniofacial Research)
Background: A significant percentage of the world is distressed due to the widespread and aggressive head and neck squamous cell carcinoma (HNSCC). The prognosis for people with HNSCC remains grim, despite progress in treatment techniques. This underscores the pressing demand for the discovery of novel biomarkers to enable early detection and improve prognostic categorization. Objective: The present study aims to identify the expression of the PNMA1 gene in HNSCC with clinicopathological characteristics, prognosis, and association of immune cells infiltration. Methods: The TCGA-HNSCC dataset first evaluated PNMA1 expression and its relationship to clinical aspects of HNSCC. Following that, oral squamous cell carcinoma (OSCC), a primary HNSCC type, is used to validate PNMA1 mRNA expression, via quantitative reverse transcription PCR (RT-qPCR). The Kaplan-Meier plot was used to assess survival rates, and the Tumour Immune Estimation Resource (TIMER) database was used to examine the relationship between PNMA1 and immune cells infiltration. Results: The expression of PNMA1 significantly increased in HNSCC and OSCC tumors. Significant correlations have been found between the increased PNMA1 expression and clinicopathological characteristics of HNSCC, such as tumor stage, grade, metastasis, HPV status and patient survival. PNMA1 expression also correlated with immune cell infiltration and immune regulator genes. Conclusion: In conclusion, the present study demonstrated that the PNMA1 expression significantly increased in HNSCC and was associated with HNSCC patient's prognosis. Hence, PNMA1 could serve as a novel prognostic biomarker and a promising therapeutic target for HNSCC.